Spiritual Heritage and Great Silk Road Traditions are an Important Factor in The Development of National Tourism in Uzbekistan - Djuraeva Gavhar Normuratovna; Abdullaeva Komila Timurovna (Universitas Muhammadiyah Sidoarjo, 2020)
The article analyzes historical factors affecting the development of national tourism in Uzbekistan. The issues of travel through the Great Silk Road, diplomatic relations, travelers of Islamic Eastern countries, their works, the role and importance of travelers of Eastern and Western countries in trade-economic, socio-political and spiritual-cultural relations between Eastern and Western countries were analyzed. These projects focus on the promotion of tourism as one of the efficient mechanisms for enhancing cooperation between countries. On the one side, it is a colorful region rich in tourism destinations and tourist products, with a remarkable heritage, variety of natural conditions and cultural traditions. On the other hand, it is an area with dramatically varying socio-economic development, which influences the tourism industry. For centuries, the Silk Road has been the most significant and productive way for the nations of Asia and Europe to integrate. It was through it that products, knowledge, technologies and cultures were interchanged, which eventually promoted the development of cities, regions, states and civilizations. For the creation of a service called the